MEMBERDAYAKAN LANSIA MELALUI EKOPRINT: MENINGKATKAN KETERAMPILAN, KESEJAHTERAAN, DAN KEBERLANJUTAN LINGKUNGAN MELALUI BANK SAMPAH - Husniati, Renny; Pangestuti, Dewi Cahyani; Shinta, Nurendah; Widodo, Purwanto; Setiadi, Iwan Kresna (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The empowerment of the elderly through environment-based and creative economic activities has been demonstrated to have great potential to improve their quality of life, both socially and economically. The objective of this Community Service Program is to enhance the productivity of the elderly by leveraging a waste bank as a resource for the production of eco-print products. The community service program was implemented in Benda Baru Village, Pamulang District, South Tangerang City, involving elderly participants from the Elderly Health Post (Posyandu Lansia) and local waste bank managers. The program was meticulously designed, comprising multiple phases. These phases included initial coordination, socialization, technical training in eco-printing, production assistance, and evaluation and follow-up. The outcomes of this study indicate an enhancement in the participants' proficiency in processing natural materials from the waste bank into eco-print products with market value, including fabric, bags, and tablecloths. The program's social impact was multifaceted, including the enhancement of self-confidence and social engagement among the elderly participants, a reduction in loneliness, and the strengthening of social bonds within the community. Participants have begun to utilize their newly acquired skills to produce eco-print products, thereby opening up micro-business opportunities based on these products. Significant environmental impacts have been observed, including a reduction in organic waste and an increase in environmental awareness among participants, which can be attributed to the implementation of waste management through the waste bank. However, challenges such as limitations in product marketing and inconsistent raw material supply must be addressed. This program demonstrates that eco-print-based empowerment and waste management for the elderly can create sustainable positive impacts for the elderly, the local economy, and the environment. In the future, the program should concentrate on advanced training in marketing and the use of digital platforms to expand the market reach of the products produced.